Alapaha General, Store Manifest - (:unkn) unknown (My University, 1851)
The Alapaha Store manifest is a handwritten accounting of the goods and customers that visited the Alapaha Store, a post road general store in Lakeland, Georgia, (which used to be called Alapaha-Alapaha became Milltown which became Lakeland) between January - December, 1851. The manifest was repurposed as a scrapbook around 1870 and features newspaper clippings from national and regional papers with excerpts of poetry, bible sermons, and stories.
Store Manifest
Pages have been ripped from the manifest or are missing.
Keywords: Lanier County (Ga.); Lakeland (Ga.); Georgia; Account books